2018
DOI: 10.2118/185065-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Imbibition Oil Recovery in the Duvernay Formation

Abstract: Summary In this study, we evaluate the wettability of shale plugs from the Duvernay Formation, which is a self-sourced reservoir in the Western Canadian Sedimentary Basin. We use reservoir oil and flowback water (brine) to conduct air/liquid contact-angle and air/liquid spontaneous-imbibition tests for wettability evaluation. We characterize the shale samples by measuring pressure-decay permeability, effective porosity, initial oil and water saturations, mineralogy, and total-organic-carbon (TOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…332 A recent study of imbibition oil recovery from the oil-wet Duvernay shale formation provided a comparison of distilled water, produced brine, a nonionic surfactant, and clay stabilizer (Table 6, entry 16). 67,326,327 The greatest oil recovery was attained with the surfactant solution, which was attributed to surfactant solution being capable of displacing oil from hydrophilic pores and a portion of the hydrophobic pores. These researchers concluded that water cannot displace oil from hydrophobic organic pores.…”
Section: Spontaneous Imbibition Experimentsmentioning
confidence: 99%
“…332 A recent study of imbibition oil recovery from the oil-wet Duvernay shale formation provided a comparison of distilled water, produced brine, a nonionic surfactant, and clay stabilizer (Table 6, entry 16). 67,326,327 The greatest oil recovery was attained with the surfactant solution, which was attributed to surfactant solution being capable of displacing oil from hydrophilic pores and a portion of the hydrophobic pores. These researchers concluded that water cannot displace oil from hydrophobic organic pores.…”
Section: Spontaneous Imbibition Experimentsmentioning
confidence: 99%
“…Other observations also suggest that microstructure and characteristics of organic matter pores may be related to wettability. Thus, Yassin and co-workers , and Begum et al analyzed the influence of kerogen matter-hosted pores on shale wettability for a broad range of samples (16 Upper Duvernay and 147 Lower Duvernay shale samples). A cross plot of ϕ eff (effective porosity) and k Decay (permeability) vs TOC was created which demonstrated that ϕ eff generally increased with increasing TOC, suggesting that most pores were located inside the organic matter (OM).…”
Section: Review Of Shale Wettability Datamentioning
confidence: 99%
“…A small part of oil could be removed from the rock surface by buoyancy, exposing the rock surface to the water, thus slightly changing the surface wettability. The positive effect of IFT reduction on WA can be found in the studies conducted by Alvarez and Schechter, 39 Liu et al, 40 and Yassin et al 41 3.4. Wettability Alteration by Chelating Agents + VES in Synthetic Seawater.…”
Section: Wettability Alteration By Ves In Syntheticmentioning
confidence: 83%